Auto-Sorting Waste Detection System for Service-Oriented Well-Being Solution - Belal, H. M.; Ahda, Sabrina Washiatul (UUM Press, 2018)
Service-based value creation for well-being solution is an urgent requirement in business and social sustainability. Proper management of waste can help to ensure service-oriented value; thereby business and society can enjoy sustainability. From the macro perspective, it can be observed that waste is a phenomenal volume of mixed complex materials that can become useless output if one does not put into place a step of circular solution, which is recycle, reuse, and reduce (3R). However, before any of the 3R can be a success, waste must be sorted by separating them into organic vs. inorganic, and recyclable vs. unrecyclable to make the process of 3R more effective. Usually, most people are less aware or do not have enough knowledge regarding storage of their waste. This study proposes an effective and a prominent system to sort out and detect trash in an auto-waste sorting detection machine. The qualitative method will be conducted for data collection through semi-structured interviews with experts of solid waste management. This research can potentially help to improve the realization of the mandatory source separation required by the Malaysian government and the implementation of Act 672 about waste separation at source and recycling in Malaysia.